Relationship between the number of neurosurgical ICU and hemorrhagic stroke mortality in advance level hospital in Thailand - Russameyoongtong, Naruepak; Veerasarn, Kullapat (Thai Journal of Neurological Surgery, 2025)
Hemorrhagic stroke is not only a common neurological disease but also being a leading cause of death. The authors explored the mortality of hemorrhagic stroke patients in the advance level hospital who have neurosurgical ICU (NSICU) compared to the hospital without neurosurgical ICU (GenICU) to find out how much better the stroke mortality is. Of all advance level hospital in Thailand, there are 17 hospitals have NSICU with total beds of 175, no NSICU (using GenICU) 15 hospitals. The mortality in the NSICU group is 22.64 significantly better than GenICU group (33.71%). The more NSICU beds, the less mortality for hemorrhagic stroke the hospital will get. Despite the limitation of the clinical data of the patients, this study finds out the important of neurosurgical ICU to improve the mortality of hemorrhagic stroke in advance level hospital in Thailand.